PENGARUH ECONOMIC SHOCK TERHADAP PENERIMAAN PAJAK PADA KANTOR WILAYAH PAJAK DI INDONESIA - Wahyudi, Eddi; Sanim, Bunasor; Siregar, Hermanto; Nuryartono, Nunung (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2009)
The purpose of this research is to analyse how far the economic shock influence upon the tax revenue performance in the regional tax office. The research is conducted using yearly time series data within 2002 to 2007 and also applying two indicators: Income Tax and Value Added Tax. By using the panel data analysis the result upon 31 Kanwil Directorate General of Tax (DGT) whole Indonesia it is known that the fluctuation variable of Tax Early Warning System (TEWS) gives positive effect to the tax income performance at Kanwil Khusus, Kanwil WP Besar 1 and 2, Kanwil Jakarta Selatan and Kanwil Jakarta Pusat. Overall the entire research result explains that Indonesia economic condition until he year of 2007 is still in the small open economy status and identically to New Keynes theory. The conclusion is as if the research about the Indonesia business cycle previously and consistent with the initial assumption applied.